Армянское посольство Публия Клодия - Литовченко, С. Д. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryS. Litovchenko. The Armenian Embassy of Publius ClodiusIn his letters, Cicero says that in the first half of 59 BC representatives of the «first triumvirate» intended to send Publius Clodius, who had just passed from the patricians to the plebeians, to the embassy to Tigranes II the Great. Most of the researchers, based on reports of Cicero, claimed that the embassy did not have a major foreign policy values and Clodius refused to participate in it because of the fact that the trip was absolutely humiliating. But the analysis of the political situation in Rome suggests that the embassy had a large enough value for the foreign policy of the Roman — Roman ambassadors were to tell Tigranes II to grant him the status of “friend and ally of Rome.” Refusal to participate in Claudia embassy was not due to its insignificance, this refusal can be explained by the inability of Publius Clodius to participate in the elections of plebeian’s tribunes for the next 58 BC.Key words: Rome, Tigranes II, Cicero, Publius Clodius, Armenia.